The Effect of Flash Sale on Impulsive Buying with Positive Emotion as Mediating Variable among Shopee Users in Malang City - Hermawan, Doni; Rofiq, Ainur (East Asian Journal of Multidisciplinary Research, 2024)
The expansion of the internet has revolutionized how businesses engage with global customers, significantly altering commerce and daily life in Indonesia. This digital transformation has led to the rapid growth of e-commerce, fostering innovation in digital business practices and the emergence of new marketplaces. This study investigates the influence of flash sales on impulsive purchasing behavior, considering the mediating role of positive emotions among Shopee users in Malang City. Employing a quantitative, explanatory descriptive methodology, data were gathered from 300 respondents using purposive sampling. The results indicate that: 1) Flash sales have a positive and significant effect on impulsive buying behavior, 2) Positive emotions also positively and significantly affect impulsive buying behavior, and 3) Positive emotions significantly mediate the relationship between flash sales and impulsive buying behavior on Shopee.